Efficiency and safety of Buzhong Tiaogan granule for treating the colorectal cancer patients with liver metastasis: study protocol for a multicenter randomized controlled trial - Hao, Shu-Lan; Zhou, Yan-Chen; Li, Xiao-Li; Zhong, Qi-Ming; Liu, Li-Kun; Gao, Yu; Wang, Xi-Xing; Yang, Wen-Hui; Yang, Li-Fang (Frontiers in Medicine, 2024)
Objective To evaluate the clinical efficacy and safety of Buzhong Tiaogan granule (BTG) in treatment of colorectal cancer patients with liver metastasis and provide high-level evidence for clinical practice. Methods and analysis This is a prospective, randomized, controlled, multi-center controlled trial. A total of 210 patients diagnosed with spleen deficiency and liver depression, as well as colorectal cancer liver metastasis (CRLM) of the stasis and toxin interception type, will be enrolled in the study. The participants will be randomly allocated into two groups: a treatment group that will receive BTG plus conventional first-line anti-tumor therapy and a control group that will receive conventional first-line anti-tumor therapy alone. The primary outcomes are progression-free survival (PFS) and quality of life scores. The secondary outcomes are as follows: (a) overall survival (OS); (b) objective response rate (ORR); (c) liver-specific progression-free survival; (d) disease control rate (DCR); (e) traditional Chinese medicine (TCM) syndrome score; (f) Piper Fatigue Scale, and (g) Karnofsky Performance Status (KPS) score. Safety evaluations will be conducted throughout the study period. Discussion The results of this trial will provide scientific and objective data necessary for the evaluation of the efficacy and safety of BTG for colorectal cancer patients with liver metastasis. Clinical trial registration The trial was registered at ClinicalTrials.gov (ChiCTR2400084861) on May 27, 2024.